The Effect of Profitability, Liquidity, Leverage, Dividend Policy and Foreign Ownership on Firm Value - Refika Nadia; Pratana Puspa Midiastuty; Eddy Suranta; Danang Adi Putra (Yayasan Ilomata, 2023)
This research aims to empirically test the influence of profitability, liquidity, leverage, dividend policy and foreign ownership on firm value. The sample used in this research is manufacturing companies listed on the Indonesia Stock Exchange with a research period of 2018-2022. The sampling technique used a purposive sampling method with predetermined criteria there were 55 observations. The research results provide empirical evidence that leverage and foreign ownership have a positive and significant effect on firm value, while profitability, liquidity and dividend policy have no effect on firm value. This research provides implications for capital structure theory which states that the use of higher leverage will increase firm value and also provides implications for agency theory in explaining the relationship between foreign ownership and firm value and provides implications for signal theory in explaining the relationship between profitability and dividend policy on firm value.